A Comparative Study of Smooth Insertion of Laryngeal Mask Airway with Propofol and Thiopentone Combined with Midazolam - Khatoon, Syeda Nafisa; Tipu, Md Rezaul Hoque; Hasan, Sanjida; Billah, KM Baki; Chowdhury, Gulshan Ara; Alam, AKM Shamsul (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Successful insertion of Laryngeal Mask Airway (LMA) requires sufficient depth of anesthesia and depression of airway reflexes to avoid gagging, coughing and laryngeal spasm. The LMA is popular because it is easy to insert and it provides a secure airway for the patients who breathe spontaneously. Indeed, the intravent LMA instruction manual specifically recommends propofol for induction of anesthesia during LMA insertion. As a matter of fact Propofol and LMA insertion has become synonymous. However, there are some problems related to the use of propofol, for example, relatively high cost. This observational study was conducted to compare efficacy and safety of propofol and thiopentone -midazolam in smooth insertion of LMA and the hemodynamic changes over time in both groups. Methods: The study was done in the Department of Anesthesiology, Chittagong Medical College from July, 2012 to December, 2013. All the patients scheduled for elective surgical procedures under general anesthesia fulfilling the inclusion criteria, were the study population. Data was analyzed by computer based software SPSS-21. Results: Overall LMA insertion condition was improved better by the use of midazolam with thiopentone sodium (Group B) than propofol (Group A). The drug regime used in group A (Propofol) was expensive than group B (midazolam with thiopentone sodium) with indifferent hemodynamic stability in both groups. Mean ages of patients were 32.43 years ± SD- 10.67 years in group A and 33.5 years ± SD- 10.63 years in group B. Conclusion: In the perspective of our study, for smooth insertion of LMA midazolam-thiopentone sodium regime is cheaper and can be effectively and safely used over propofol regime. Chatt Maa Shi Hosp Med Coll J; Vol.17 (1); Jan 2018; Page 38-41